2019
DOI: 10.1200/po.18.00263
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Genomic Variants in Matched Primary Breast Cancer, Metastatic Tumor, and Circulating Tumor DNA: The MIRROR Study

Abstract: PURPOSE Genetic heterogeneity between primary tumors and their metastatic lesions has been documented in several breast cancer studies. However, the selection of therapy for patients with metastatic breast cancer and the search for biomarkers for targeted therapy are often based on findings from the primary tumor, mainly because of the difficulty of distant metastasis core biopsies. New methods for monitoring genomic changes in metastatic breast cancer are needed (ie, circulating tumor DNA [ctDNA] genomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…S10). Further, consistent with the notion of ctDNA providing a global view representing genomic changes from diverse metastatic sites (Moreno et al 2019), ctDNA also captured variants that were not detected in the tumor (58.6% of ctDNA variants were unique to ctDNA; n = 521). Third, the tumor transcriptome data generally supported reduced post-treatment JAK1 signaling, with the notable exception of STAT1 expression, which increased post-treatment (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…S10). Further, consistent with the notion of ctDNA providing a global view representing genomic changes from diverse metastatic sites (Moreno et al 2019), ctDNA also captured variants that were not detected in the tumor (58.6% of ctDNA variants were unique to ctDNA; n = 521). Third, the tumor transcriptome data generally supported reduced post-treatment JAK1 signaling, with the notable exception of STAT1 expression, which increased post-treatment (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…The primary goal of deep sequencing is to detect rare mutated DNA copies shed by tumors (ctDNA) and differentiate them from wildtype copies that are simultaneously released from normal hematopoietic cells undergoing apoptosis. Comparative sequencing studies have shown that specific mutations in ctDNA vs. matched primary tumor tissue are generally concordant (43,44), however, temporal spacing (e.g., timing of sample collection) and tumor heterogeneity could also lead to discrepancies (45). Overall, these data suggest that ctDNA can complement tissue sequencing to find actionable biomarkers.…”
Section: Circulating Tumor Dna Andmentioning
confidence: 90%
“…Comparative sequencing studies have shown that specific mutations in ctDNA vs . matched primary tumor tissue are generally concordant ( 43 , 44 ), however, temporal spacing (e.g., timing of sample collection) and tumor heterogeneity could also lead to discrepancies ( 45 ). Overall, these data suggest that ctDNA can complement tissue sequencing to find actionable biomarkers.…”
Section: Liquid Biopsy Biomarkers: Characteristics and Technology Pla...mentioning
confidence: 99%
“…In cases where biopsy samples are difficult to retrieve and the quality and quantity of tissue specimens are insufficient for tissue-based CGP, liquid biopsy should be considered the assay of choice. Furthermore, if patients present with multiple lesions or metastases, liquid biopsy should be preferred due to its ability to detect intertumoral heterogeneity, which could be missed by a single tissue testing [145][146][147]. The detection of spatial tumor heterogeneity was highlighted in a study that sequenced paired primary tumor, metastatic tissue, and plasma cfDNA of breast cancer patients [146].…”
Section: Availability Of Excision Tumor Tissue Quality and Quantity O...mentioning
confidence: 99%
“…Furthermore, if patients present with multiple lesions or metastases, liquid biopsy should be preferred due to its ability to detect intertumoral heterogeneity, which could be missed by a single tissue testing [145][146][147]. The detection of spatial tumor heterogeneity was highlighted in a study that sequenced paired primary tumor, metastatic tissue, and plasma cfDNA of breast cancer patients [146]. Plasma cfDNA detected up to 97% of alterations from primary and metastatic tissues, and 13 of the variants in metastatic tumors were exclusively detected from ctDNA, and not in the corresponding primary tumors [146].…”
Section: Availability Of Excision Tumor Tissue Quality and Quantity O...mentioning
confidence: 99%